An Analytical Examination of Andragogical Principles in the Implementation of Adaptive Technology for Adult Education - Darmawan, Daddy; Sasmita, Karta; Dewi, Intan Purnama (Edukasi, 2024)
The use of technology in education tailors’ content and teaching methods to meet individual learning needs; however, significant challenges remain in its practical application. This study analyzes the implementation of adaptive technology in adult education and applies andragogical concepts in personalized, interactive, and problem-based learning. The research employed a quantitative survey with 249 respondents from various educational institutions and used Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the relationship between adaptive technology and andragogical learning strategies. The results indicate that adaptive technology has a positive and significant impact on andragogical learning strategies. Indicators such as technology accessibility, personalized learning, interactivity, and system integration support problem-based learning, self-directed learning, continuous feedback and evaluation, and contextual learning. The high outer loadings values demonstrate the significant contribution of each indicator to their constructs, and an R Square value of 0.369 indicates that 36.9% of the variability in andragogical learning strategies can be explained by adaptive technology. Adaptive technology can improve the quality of adult education by providing a more personalized, independent and interactive learning experience. So adequate infrastructure and educator training are needed to realize the full potential of adaptive technology.